Caste, Courts and Business - Tanika Chakraborty; Anirban Mukherjee; Sarani Saha; Divya Shukla (Institute of Labor Economics (IZA), 2022)
We study the role of formal institutions of contract enforcement in facilitating investments in small and medium firms(MSME). In a framework where established entrepreneurs can enforce contracts informally using their network ties and hierarchical advantage, we argue that an efficient formal judiciary helps entrepreneurs without any ties to informal business networks, disproportionately more. We test our theoretical prediction using a novel administrative panel-data from Indian courts and the nationally representative MSME survey data. Empirically, we treat entrepreneurs from disadvantaged castes (SC-ST) as those without traditional business-network ties. We find that improvement in court quality has a disproportionately larger impact on the investment decisions of SC-ST entrepreneurs. On average, if the time taken for a court to clear all existing cases reduces by 1 year, the initial gap in the probability of investing, between SC-ST and other entrepreneurs, gets reduced by 0.6-0.7 percentage points.
Keywords: K12; L26; O17; 330; judiciary; Duration Index; MSME; entrepreneurship